Novel concepts in vascular stent design: Can stent be personalized through computational fluid dynamics? - (:unkn) unknown (Bentham Science Publishers B.V., 2015)
In the last few decades, popularity of coronary interventions has risen rapidly. Widespread use of coronary stents and high number of patients with atherosclerosis made the stents the focus of attention by the industry. This has led the stent technology to evolve rapidly. The aim of this review is to outline the evolution of coronary stents and the stent components in the timeline. Pharmacogenomics, personalized medicine and computational fluid dynamics can help us to design individualized stents. © 2014 Bentham Science Publishers.
Keywords: Computational fluid dynamics; Personalized medicine; Vascular stent